2001
DOI: 10.1002/1096-9098(200102)76:2<89::aid-jso1016>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy in proximal gastric cancer: Frequency of lymph node metastasis to the splenic hilus

Abstract: Based on our data lymph node metastasis to the splenic hilus is rarely observed in proximal gastric cancer and only found in advanced cancer (UICC IIIb/IV) especially in tumors of the greater curvature and of Borrmann type IV cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 16 publications
3
45
0
1
Order By: Relevance
“…In Germany, No. 10 metastasis was observed only in advanced cancer, particularly in tumors located in the greater curvature and/or type 4 tumors [26]. Our current study showed that splenectomy adversely affected survival in pSE and pN2, while there was no significant difference in survival rates in pMP, pSS, pN0, and pN1 and among Stage II, IIIA, and IIIB.…”
Section: Discussionmentioning
confidence: 50%
“…In Germany, No. 10 metastasis was observed only in advanced cancer, particularly in tumors located in the greater curvature and/or type 4 tumors [26]. Our current study showed that splenectomy adversely affected survival in pSE and pN2, while there was no significant difference in survival rates in pMP, pSS, pN0, and pN1 and among Stage II, IIIA, and IIIB.…”
Section: Discussionmentioning
confidence: 50%
“…It was related to the conviction that removal of the lymph nodes located in the splenic hilum may be a prognostic marker. Several studies have concluded that the disadvantages of splenectomy outweigh the prognostic benefits for patients with gastric cancer [22, 31, 32]. The results of our analysis convinced the Gdansk surgical team to change the strategy of management and to improve the surgical quality [33].…”
Section: Discussionmentioning
confidence: 59%
“…Splenectomy was performed (n = 35) in cases of proximal gastric carcinoma (types II and III) and in cases of metastatic infiltration of the splenic hilar nodes (No. 10), but not as a general rule [16]. …”
Section: Methodsmentioning
confidence: 99%